Tinjauan Kriminologi Terhadap Kekerasan Seksual Yang Dilakukan Oleh Guru Pada Anak - Anizha, Siti Noor; Puluhulawa, Moh. Rusdyanto U; Towadi, Melisa (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Sexual violence is one of the major crimes like other crimes that affects and has an impact on the destruction of the social fabric of the Indonesian nation. According to Islam, sexual violence itself is a form of cultural values ​​and social backgrounds that deviate from a human perspective. Crimes like this damage the human side for both women and children in accordance with Article 82 in Law Number 23 of 2002 concerning Child Protection. This research is to find out the factors of sexual violence perpetrated by teachers on children, to find out the mode of sexual violence perpetrated by teachers on children, to find out the legal protection given to children as victims of sexual violence. This research uses normative juridical research, namely by examining library materials or secondary data. Research that refers to legal norms contained in laws and regulations. Research results Children still do not understand the dangerous conditions around them because they do not have knowledge and self-control. The perpetrator's mode by persuading the child to feel comfortable with the perpetrator and persuading the child to want to have sex and the legal protection that can be given to children who are victims of sexual crimes are regulated in Law no. 35 of 2014 concerning Amendments to Law no. 23 of 2002 concerning Child Protection.